2017
DOI: 10.1016/j.sbi.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral intasomes arising

Abstract: Retroviral DNA integration takes place within the context of the intasome nucleoprotein complex. X-ray crystal structures of functional spumaviral intasomes were previously revealed to harbor a homotetramer of integrase, and it was generally believed that integrase tetramers catalyzed the integration of other retroviruses. The elucidation of new structures from four different retroviruses over the past year has however revealed this is not the case. The number of integrase molecules required to construct the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…A series of X-ray crystallographic and single-particle cryogenic electron microscopy (cryo-EM) structures determined over the past decade has clarified that the number of IN molecules required to build the intasome differs depending on the type of retrovirus (reviewed in Ref. 36). Seven retroviral genera are grouped into two subfamilies of Retroviridae: Spumavirinae, solely harboring the spumaviruses, and Orthoretrovirinae, which encompass the lentiviruses, such as HIV-1, as well as ␣-, ␤-, ␦-, ⑀-, and ␥-retroviruses.…”
Section: Intasome Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of X-ray crystallographic and single-particle cryogenic electron microscopy (cryo-EM) structures determined over the past decade has clarified that the number of IN molecules required to build the intasome differs depending on the type of retrovirus (reviewed in Ref. 36). Seven retroviral genera are grouped into two subfamilies of Retroviridae: Spumavirinae, solely harboring the spumaviruses, and Orthoretrovirinae, which encompass the lentiviruses, such as HIV-1, as well as ␣-, ␤-, ␦-, ⑀-, and ␥-retroviruses.…”
Section: Intasome Structure and Functionmentioning
confidence: 99%
“…IN processes the viral DNA ends in the context of the initial stable synaptic complex (SSC), yielding the cleaved synaptic complex (CSC) after viral DNA hydrolysis. The target capture complex (TCC) describes the CSC bound to target or host DNA, whereas strand transfer yields the strand transfer complex (16, [35][36][37]43). The overall conformation of the PFV intasome structure changes little as the complex morphs from the SSC to the strand transfer complex and promotes IN 3Ј processing and strand transfer activities (16, 35,37,43,44).…”
Section: Intasome Structure and Functionmentioning
confidence: 99%
“…Intriguing new cryo-EM studies have identified structures for HIV IN containing more than four IN molecules. The relative contributions of these higher order structures to integration and interactions with elements of the PIC remain uncertain and are topics of active investigation [ 135 ]. The development of a new class of IN inhibitors, called allosteric integrase inhibitors (ALLINIs), will be particularly useful probes in understanding the role of higher order structures in HIV IN (reviewed by Feng et al [ 136 ]).…”
Section: Integration: the Central Event In Hiv Replicationmentioning
confidence: 99%
“…IN is capable of assembling the STC with the product of the concerted integration reaction (a branched viral/target DNA substrate) and the SSC that utilizes only viral DNA substrates in vitro (1)(2)(3)(4)(5)(6). Our results here suggest that the soluble form of the RSV STC may not address what regions or residues of IN are necessary for assembly as well as what is observed with the SSC.…”
Section: Assembly Of Retrovirus Tetrameric and Octameric Intasomesmentioning
confidence: 77%